Advancing the Moral legitimacy of digital platforms as gatekeepers: a critical analysis from a political corporate social responsibility perspective - Dirk Ulrich Gilbert; Stephanie Schrage; Michael Behnam (Journal of Business Economics, 2024)
Abstract This study focuses on digital platforms, such as Google or Meta, that function as “gatekeepers” that dominate their respective markets. They face serious moral legitimacy issues, due to their power to act as private rule-makers in underregulated digital spheres. Such legitimacy issues have remained underexplored thus far, as have gatekeepers' options for addressing them. Yet moral legitimacy represents a vital resource for organizations, as a justification of their essential right to exist. Drawing on recent advances in political corporate social responsibility theory, this study offers a systematic conceptualization of how gatekeepers can exhibit ethical responsibility in their efforts to gain, maintain, and sustain their moral legitimacy. This systematic conceptualization encompasses different agreement-seeking procedures, online deliberation, a hybrid governance approach that combines regulation and self-regulation, and the provision of public goods.
Keywords: 330; Digital platforms; Political CSR; Gatekeepers; Deliberative democracy; Online deliberation; Moral legitimacy